Using partial least squares approach to predict the impact of transformational leadership on employee commitment to organizational change - Gelaidan, Hamid Mahmood; Ahmad, Hartini (Medwell Journals, 2013)
The aim of this study was to examine the relationship between transformation leadership and employee commitment to organizational change by utilization Partial Least Squares (PLS) approach. Data were collected through a survey among employees who work in a Yemeni public sector organization.The finding showed that idealized influence and individual consideration were found significantly and positively related to all dimensions of employee commitment to change. While the inspirational motivation and intellectual stimulation have different finding with each dimensions.The limitations of this study may include several issues that may lead to future studies.This study contributes to the change management literature by integrating the linkage between leadership and employee commitment to change.It is the first study conducted by using PLS with stated model and conducted in least developed country, such as Yemen.